Peito de frango marinado com gengibre : efeito da atividade proteolítica do extrato bruto e da temperatura nas características físico-químicas e sensoriais - Menezes, Marcella Dias Marinho (2019)
The marination technique, including in the liquid marinating salts and phosphate and the use of exogenous proteolytic enzymes, obtained from natural sources such as vegetables, to improve the sensorial attributes, represents an alteration to improve the quality of chicken meat. In this context, the present study had the objective of evaluating the effects of application of the crude enzymatic extract of ginger at concentrations of 1, 3, 5, 7% w / v, water retention capacity, weight loss per cooking, shear force and myofibrillar fragmentation index (MFI) of chicken breast cuts (Pectoralis major muscle). Afterwards, five treatments were tested to verify the influence of different temperatures (40, 50, 60, 70 and 80 ° C) on breasts of marinated chicken with and without crude, evaluating post-bake weight loss and the shear force of the cuts. The sensorial acceptance test and the intention of purchase test were performed. There was a significant decrease in post-cooking weight loss (P <0.05) from treatments in which the chicken breasts were injected with crude ginger extract in relation to the control. Among the treatments with addition of extract, only the chicken breast with 1% crude ginger extract differed significantly from the others (P <0.05), presenting greater weight loss after cooking. In relation to the water retention capacity, a significant increase (P<0,05), was observed for chicken breasts with extract addition in relation to the control treatment, regardless of the extract concentration tested. There was a decrease in the value of shear force (P <0.05) and an increase in myofibrillar fragmentation index (P <0.01) in the treatments with addition of ginger extract in relation to the control treatment. The interaction between the marination factors with and without addition of ginger extract and temperature (40, 50, 60, 70 and 80 ° C) was significant (P <0.05) for weight loss after cooking and texture with improvements in these characteristics in relation to control. By the sensorial acceptance test, the breasts of marinated chicken with the addition of 3% of ginger extract had greater acceptance in relation to the others.